RECOGNITION AND THE CHARACTER OF SENECA'S MEDEA. (December 2016) - Bexley, Erica
Abstract : This article examines the character and identity of Seneca's Medea. Focusing on the recognition scene at the end of the play, I investigate how Medea constructs herself both as a literary figure and as an implied human personality. The concluding scene of Seneca's Medea raises crucial questions about self-coherence and recognisability: in contrast to other moments of anagnōrisis in Greco-Roman drama, it confirms the pre-existing facets of Medea's identity, rather than revealing new ones. This concept of recognition as self-confirmation is also integral to Seneca's Stoic view of human selfhood, and Medea's use of Stoic principles in this play reinforces her dual status as textual entity and quasi-person.